Evaluation of Public Policy on Street Children (Case Study of the Bandung City Social Services Agency) - Rosialani, Resa; Muhammad Ridwan Caesar; Edi Iskandar; Iin Endah Setyawati (Social Impact Journal, 2025)
This study aims to evaluate the public policy on street children enforcement implemented by the Social Services Department of Bandung City. The issue of street children in Bandung City is a complex social phenomenon that requires serious attention from the Social Services Department. Despite various enforcement efforts, the number of street children remains fluctuating from year to year. The study also identifies the challenges and efforts made in its implementation.  This study uses a descriptive qualitative method with a case study approach. Data was collected through in-depth interviews, direct observation, and documentation, using the Miles and Huberman data analysis model, which includes data reduction, data presentation, and drawing conclusions. Informants in the study were purposively selected from the Social Services Agency, Satpol PP, and street children as the target group of the policy. Policy evaluation was conducted based on six indicators from William N. Dunn (Dailati, 2018), namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of the study indicate that policy evaluation is not yet fully optimal across all indicators. The obstacles faced include budget constraints, inadequate facilities, lack of coordination between institutions, and minimal involvement of street children's families. Efforts that have been made include outreach, guidance, and cross-sectoral cooperation, but these have not been able to resolve the root of the problem comprehensively. Therefore, a more integrative, sustainable, and child-friendly policy strategy is needed.